Proyecto de factibilidad para la implementación de un centro de equinoterapia para personas con capacidades especiales para la ciudad de Cuenca - Moyano Lara, Rosa Isabel (2015)
The project aims to implement a run Equine Center in the city of Cuenca as an alternative therapy for people with disabilities have a better quality of life. To begin with the study of this project has set an overall target named: Prepare a Draft Feasibility for the Implementation of Equine Center in the city of Cuenca for people with disabilities, which raised specific objectives that served as guide for the study. To meet this primary objective methods, techniques and procedures whereby research, develop and test the veracity of the project were used. The methods used were: Deductive, which allowed based on the theoretical concepts related to the realization of an investment project application in the development of market research, technical, organizational, economic and financial; Inductive: This method based on the peculiarities found in the project feasibility, generalizing conclusions and recommendations were used. Note: The following techniques are applied It allowed to know how to carry out this service today as an alternative for people with disabilities therapy. Survey: Applied to a representative sample of the population of families in the city of Cuenca to determine the needs and preferences of the target market in relation to the service of Equine vital to the establishment of demand, supply and demand unmet service information bid. Total 390 Survey, total study population 17,012 persons with disabilities. For the study and analysis of the Offer, parents and relatives of the population of the city of Cuenca was surveyed. 6 The analysis in the development of each of the phases of the project feasibility allowed to reach the following conclusions: 1. Market Research Company determines that it is feasible to implement it according to data obtained an unmet demand was obtained 13,848 people with disabilities for the first year. Of the total investment own member contributions amount to a value of $ 66893,06 representing 40%; and credit worth $ 100339,6 with a percentage of 40%. Giving a total of $ 167232,66; analysis Breakeven envisioned that for the first year the company must use an installed capacity of 58% and should have sales of $ 92311,96 for the firm does not win or lose. The financial evaluation indicates that the NPV is 555866, an IRR of 80,86%, the company will recover the capital in 3 years, 2 months and 19 days; that for every dollar invested company earns 0.43 cents, and that the company supports an increase of 29,4% costs and declining revenues 21%, determined that implementing this type of business in the City of Cuenca is feasible. Based on the results, it is recommended to implement the project as it will give a significant returns for its investors thus contributing to the improvement of the Features of this City.